2015
DOI: 10.1097/ajp.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Pain Self-efficacy Mediates the Relationship Between Depressive Symptoms and Pain Severity

Abstract: These findings suggest that pain management and rehabilitation programs for CLBP should specifically target PSE as a key aspect of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…Self-efficacy is known to be a major component in dealing with stress and pain, as well as chronic illness. 18,19 In line with recently published studies [50][51][52] the results indicate a potential long term buffering effect of self-efficacy and control beliefs on the development of disability due to LBP, which should be studied further. The influence of the potential buffering factor self-efficacy was not present in the prediction of pain intensity.…”
Section: Self-efficacysupporting
confidence: 83%
“…Self-efficacy is known to be a major component in dealing with stress and pain, as well as chronic illness. 18,19 In line with recently published studies [50][51][52] the results indicate a potential long term buffering effect of self-efficacy and control beliefs on the development of disability due to LBP, which should be studied further. The influence of the potential buffering factor self-efficacy was not present in the prediction of pain intensity.…”
Section: Self-efficacysupporting
confidence: 83%
“…The review findings support existing theories regarding the factors associated with adaptive psychological functioning despite the enduring nature of pain. In line with existing mediation research whereby the presence of positive psychological constructs facilitate greater coping and adjustment (Skidmore et al 2015;Wright et al 2011), pre and post-intervention changes in self-efficacy (Simm et al 2014) and hope (Howell et al 2015) were associated with significant improvements in psychological well-being. Although increased levels of optimism have also been found to be related to greater adjustment in individuals with chronic pain (Wright et al 2011), only one study (Flink et al 2015) included this variable, with no significant changes in optimism observed following intervention.…”
Section: Discussionsupporting
confidence: 71%
“…Residualized change scores represent the difference between the score at follow-up compared with what was predicted at baseline, 49 thereby controlling for baseline score. Residualized change scores are frequently used in studies of mediation15, 43 and are calculated by running a linear regression with the follow-up score as the outcome and the baseline score as the predictor, and saving the residual values (difference between the observed value at follow-up and the value predicted at baseline), which were then used in all subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%